Area arts funding requests top $40,000 - Wildermuth, Todd (Raton, NM Raton Range, 1995)
This article is about five Colfax County groups seeking a total of $40,150 in state grants to finance art projects ranging from Shuler Theater performances to a mask-making workshop.
Newspaper article
Master list item #: 62
File location is in the Raton file Cabinet
Keywords: Donati, Marilyn -- Executive Director Arts and Humanities Council; New Mexico Arts Division; Art and Humanities Council; Art Fund raising; Grants; Raton, New Mexico